A Model-Driven Framework for the Development of MVC-Based (Web) Application - Ahmad, Sheikh Israr; Rana, Tauseef; Maqbool, Ayesha (Arabian journal for science and engineering (2011), 2022)
Model-driven engineering is a renowned software engineering methodology for design and development of software systems with the help of various types of models. Model–View–Controller (MVC) is a popular and extensively used architectural pattern for Web application development process in different platforms. Literature review reveals that there are implementation-level deficiencies in the form of complicated structure, time taken for development and maintenance of MVC-based Web application in different MVC-based frameworks. In this article, we introduce a unique model-driven framework approach to simplify the use of MVC-based frameworks for Web application development. In our approach, we introduce a unique mechanism with the help of a UML Profile model and a model to text transformation engine to automatically generate the implementation of any (Web) application in three defined MVC-based frameworks; our approach is extensible to support more MVC frameworks. For ease, we have created an application with GUI to generate the required MVC-based framework code. The application/implementation of our unique approach is verified with two benchmark case studies; results show that we closely generate the MVC-based Web application source code which is flexible to add critical application business logic.